2006
DOI: 10.1084/jem.20051772
|View full text |Cite
|
Sign up to set email alerts
|

Platelets secrete stromal cell–derived factor 1α and recruit bone marrow–derived progenitor cells to arterial thrombi in vivo

Abstract: The accumulation of smooth muscle and endothelial cells is essential for remodeling and repair of injured blood vessel walls. Bone marrow–derived progenitor cells have been implicated in vascular repair and remodeling; however, the mechanisms underlying their recruitment to the site of injury remain elusive. Here, using real-time in vivo fluorescence microscopy, we show that platelets provide the critical signal that recruits CD34+ bone marrow cells and c-Kit+ Sca-1+ Lin− bone marrow–derived progenitor cells t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
294
1
13

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 390 publications
(314 citation statements)
references
References 41 publications
6
294
1
13
Order By: Relevance
“…The contribution of BMPC to the neointimal lesion has been well described (3)(4)(5)33), however, characterization of the progenitor cells is still controversial. Initial studies suggested that hematopoietic stem cells (HSC) may differentiate into SMC or endothelial cells; however, later studies have suggested that transdifferentiation of HSC into non-hematopoietic cells is a rare event (6, 36 -39).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The contribution of BMPC to the neointimal lesion has been well described (3)(4)(5)33), however, characterization of the progenitor cells is still controversial. Initial studies suggested that hematopoietic stem cells (HSC) may differentiate into SMC or endothelial cells; however, later studies have suggested that transdifferentiation of HSC into non-hematopoietic cells is a rare event (6, 36 -39).…”
Section: Discussionmentioning
confidence: 99%
“…These "activated" VSMC migrate to the subintima space where they continue to proliferate and, thus, form the neointimal lesion (2). Recent evidence, however, suggests that bone marrow-derived progenitor cells (BMPC) are recruited to sites of vascular injury and may also play an essential role in the development of intimal hyperplasia (3)(4)(5)(6)(7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our data reflects that PRP contains a small amount of VEGF and a relatively large amount of SDF-1α. Massberg et al [38] suggested that platelets secrete SDF-1α and recruit bone marrow-derived progenitor cells to the injured arterial site. Our previous study also showed that the sustained release of PRP accelerates the homing of hematopoietic progenitor cells to the ischemic site in vivo which reflects the contribution of the sustained release of PRP to vasculogenesis in hind limb ischemia [11].…”
Section: Discussionmentioning
confidence: 99%
“…Upon activation platelets release macrophage-migration inhibition factor (MIF) or stromal cell-derived factor-1 (SDF-1/CXCL12) [5, 22], engage a wide range of chemokine receptors like CXCR2, CXCR4, CXCR7 to impose both autocrine and paracrine effects on interacting cells in the platelet micro-environment [23]. Platelet-derived CXCL12 is a chemokine, which acts as a regulator of monocyte adhesion, survival, and migration of monocytes through its receptors CXCR4 and CXCR7 [4].…”
Section: Introductionmentioning
confidence: 99%